PENGARUH e-INFORMATION TERHADAP NIAT BELI PADA BISNIS PERHOTELAN DI SURABAYA - M Anang Firmansyah; Budi Wahyu Mahardhika (UMSurabaya Publishing, 2015)
ABSTRACT The development of internet technology, the business world is entering an era where marketing becomes cheaper and easier to access. Especially in hospitality marketing, one of the many in use by the website of hotel reservation service providers, reviews (reviewer) become a reference in the use of potential customers as additional information to strengthen the decision of the hotel to be selected.This research is useful to help managed hotel business, especially those using hotel reservation service provider website to do promotion and dissemination of information. This way of marketing e-Information is believed to be the most effective way of marketing because it involves recommendations from people close to the consumer.Therefore, in this study, the research would like to raise the impact of consumer electronics reviews on buying intentions on the website of hotel reservation service providers. Based on previous research, information quality, source credibility and number of reviews are constructed in use as independent variables that have an impact on consumers' buying intentions.The test is done by using multiple regression and simple to find a significant influence between variables. The results of this study indicate that the variables of trust to the source and number of reviews that have influence on the intention to buy on the website of hotel information provider. Keywords : e-Information, hotel, consumer reviews, information quality, source credibility, purchase intentionsCorrespondence to :anangfirmansyah.61@gmail.com, budi.w.mahardhika@gmail.com